Effects salinity on growth, chlorophyll and β-carotene concentration in Dunaliella sp. isolated from Chabahar Gulf - Sh. Enayati; A. Javanshirkhoei; Gh. Rafiei; H. Porbagher; A.A. Moradinasab (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2018)
Dunaliella sp. is from division of chlorophyte algae that has a global distribution and is abundantly reported in the coastal waters of Chabahar Bay.This algae is a euryhalin species which may support high temperatures and lack of Nitrogen conditions in the sea. Also as a response to environmental stresses it fluctuates pigment reserves specially the Beta-Carotene.The aim of this study was effects of salinity on growth, chlorophyll and β-carotene concentration in Dunaliella sp. In this study in beyond the separation and purification of Dunaliella sp. from seawater, the impact of different levels of salinity (0.5, 0.75, 1, 1.5, 2, 3 and 4 mol NaCl) on growth, the amount of chlorophyll and β- carotene were measured during a period of 4 weeks. Chlorophyll a, b and β-carotene contents were determined spectrophotometrically from algal pellets using 80% (v/v) acetone/water mixture. Results showed that the Dunaliella sp. in treatments of 0.5, 0.75, 1, 1.5, 2, 3 and 4 mol NaCl could grow, but the maximum growth of this algae and the maximum amount of β-carotene were observed in salinities between 1.5 to 2 mol NaCl (p<0.05). Parallel to growth of the algae the production of chlorophyll a and b was increased in all salinities treatments but their production causes a decrease in β- carotene production.